(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article analyzes representations of water and its intersection with figures of historical otherness observable in Argentine dramaturgy from the northern and southern regions of the country during the period 1983–2008. To develop this poetic analysis, the study draws on the theoretical and methodological orientations of ecocriticism, applied to a specific case study. The results obtained allow us to recognize and examine the topics, procedures, and intellectual positions that challenge essentialist and homogenizing ideas about the interior-other, based on the environmental conceptions specific to each territory.